(untitled) (Reflection and Critique Law Magazine, 2023)
The theme of this article is family and domestic violence against women and femicide. The following problem was investigated: why did the cases of violence against women not decrease even after the creation of protective laws for them? The following hypothesis was raised “the measures adopted are not being sufficient to reduce these forms of aggression”. The general objective is to research some reasons for the increase in these aggressions. The specific objectives are: to contextualize, clarify and analyze violence against women over time and the effectiveness of existing protections. This work is important from an individual perspective so that law enforcers learn more about the subject; for science for analyzing a social phenomenon; it adds to society by rethinking the role that women have in the social environment in which they live. This is a qualitative theoretical research lasting six months.